SIPUD (SISTEM PELAYANAN USAHA MIKRO KECIL DAN MENENGAH DESA) BERBASIS WEB PADA DESA PRINGKASAP - Komalasari, Tari; Suryani, Nining; Kurniawan, Ilham (LP2M Universitas Nurdin Hamzah, 2023)
(MSME sector services can be more effective and efficient if accompanied by the development of technology that supports them. Making business certificates (SKU) at the Pringkasap Village office is still manual, bookkeeping reports are still recorded using handwriting, MSME data collection obtained from RT data collection is also not comprehensive. In addition, the lack of socialization regarding the program for submitting a halal logo on home products is the scope of this problem. Therefore, the authors designed a computerized website for creating SKUs and data collection for UMKM to facilitate data processing, both in adding, changing, deleting, storing and searching data. The author also includes the flow of the halal certification process on the website page to expand the socialization of the program.